2020
DOI: 10.1007/s10567-020-00328-y
|View full text |Cite
|
Sign up to set email alerts
|

Components of School-Based Interventions Stimulating Students’ Intrapersonal and Interpersonal Domains: A Meta-analysis

Abstract: Many universal school-based interventions aim to stimulate students’ intrapersonal (e.g., self-esteem) and interpersonal (e.g., school climate) domains. To improve our understanding of why some of these interventions yield stronger effects than others, we identified intervention components that are related to stronger or weaker intervention effects. We systematically searched four databases (i.e., PsycINFO, PubMed, ERIC, CENTRAL) for controlled evaluations of universal school-based interventions. In total, 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 153 publications
4
23
1
3
Order By: Relevance
“…Although these improvements may represent adolescents' typical development, this finding can also indicate that R&W and usual care at schools are equally effective which, in turn, suggests that care as usual in Dutch schools is of good quality. Notwithstanding this positive finding, it is important to examine how universal school-based interventions in general, and R&W specifically, can be optimized as intervention effects of this type of intervention are generally small (e.g., Mertens et al, 2020;Tanner-Smith et al, 2018). One way to optimize R&W may be by adjusting the dosage of some components.…”
Section: Discussionmentioning
confidence: 99%
“…Although these improvements may represent adolescents' typical development, this finding can also indicate that R&W and usual care at schools are equally effective which, in turn, suggests that care as usual in Dutch schools is of good quality. Notwithstanding this positive finding, it is important to examine how universal school-based interventions in general, and R&W specifically, can be optimized as intervention effects of this type of intervention are generally small (e.g., Mertens et al, 2020;Tanner-Smith et al, 2018). One way to optimize R&W may be by adjusting the dosage of some components.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, assertiveness training has an extensive background and history, particularly since the groundbreaking work of Wolpe [18]. Evidence suggests that assertiveness training, which is the core of any training in social skills, is still present nowadays due to its effectiveness in several settings, from therapy and the treatment of severe mental illness such as schizophrenia [19] to education and the improvement of social relations and the prevention of bullying [20,21].…”
Section: Ohse Professionals: Linking Assertiveness and Sustainable Behaviorsmentioning
confidence: 99%
“…Besides examining the effectiveness of universal secondary school-based interventions at follow-up, the present meta-analysis aimed to extend previous research by examining which intervention components were related to stronger or weaker intervention effects at follow-up. Previous meta-analyses examining school-based interventions examined few, if any, components and analyzed how these relate to intervention effects immediately after the intervention (e.g., Mertens et al, 2020 ; Sheridan et al, 2019 ). To increase our understanding of long-term intervention effects, we must unravel which intervention components are related to long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding content components related to short-term intervention effects, Gaffney et al ( 2021 ) found in their meta-analysis of anti-bullying interventions that the component of ‘teaching social-emotional skills’ was related to weaker effects on bullying and victimization. The meta-analysis of universal school-based interventions of Mertens et al ( 2020 ) looked at more specific components of teaching social-emotional skills and found that focusing on emotion regulation, assertiveness, and/or cognitive coping were related to weaker effects. On the other hand, focusing on insight building and problem solving related to stronger effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation